The alkaline treatment and its influence on the physicomechanical properties of plantain pseudostem fibers - A comparative study of treated and untreated fibers - Oswaldo Hurtado-Figueroa; Humberto Varum; María Isabel Prieto; Romel J. Gallardo Amaya; Alfonso Cobo Escamilla (Heliyon)
Fibers were extracted from the pseudostem of the plantain of the variety Hartón, belonging to the order Zingiberales, family Musaceae, genus Musa, species Musa paradisiaca. The fibers were exposed to alkaline treatment to improve their physicomechanical properties for use as reinforcement in green composites. NaOH solutions of 4 %, 5 %, and 6 % by weight were prepared. The fibers were immersed for 2 h in each solution. Fibers were washed with acetic acid to remove NaOH residues and dried at room temperature. Weight loss and lignin, cellulose, and hemicellulose content were evaluated. FTIR, tensile, and elongation tests were performed. SEM images and EDS mapping allowed to conclude the phenomena that occurred in the treatments. The untreated fibers obtained a tensile strength of 37.23 MPa, in contrast to 104.26 MPa obtained by the fibers treated with 5 % NaOH solution. It was concluded that the partial elimination of impurities and waxes improved the mechanical behavior of the fibers by 180 %. Regarding elongation, the fibers treated with 4 % NaOH solution obtained the best result with 3.7 %. It was determined that the partial elimination of lignin favors elongation by 48 %. Excessive hemicellulose removal was found to cause fibril separation and detachment. Considerable contraction of vascular bundles occurred. Roughness in the fibers surface topography were improved.